Effective approximation of the solutions of algebraic equations. (March 2022) - Bilski, Marcin; Scheiblechner, Peter
Abstract: Let F be a holomorphic map whose components satisfy some polynomial relations. We present an algorithm for constructing Nash maps locally approximating F, whose components satisfy the same relations.